Intra-Accumbal administration of shRNAs against CART peptides cause increases in body weight and cocaine-induced locomotor activity in rats - Job, MO (2012)
In order to examine the effect of CART (Cocaine and Amphetamine Regulated Transcript) peptide depletion in adult rats, CART shRNAs or scrambled control shRNAs were administered bilaterally into the nucleus accumbens (NAc). There was an increase in body weight of the shRNA injected rats compared to the rats injected with the scrambled RNA. This is compatible with the data showing a role for the peptide in body weight and food intake. Also at this time, there was about a two-and-a-half fold increase in cocaine-mediated locomotion in the shRNA injected rats compared to the control rats. This finding is critical support for the hypothesis that endogenous CART peptides in the NAc inhibit the actions of cocaine and other psychostimulants. In immunohistochemical experiments on these same animals, there was a decrease in the staining density of CART peptide in the NAc of the shRNA injected rats. These data show that shRNA can reduce CART peptides in the NAc and that endogenous CART peptides influence body weight and cocaine-induced locomotor activity (LMA).